The Philosophy of Developing Women’s Rights within the Framework of Human Rights - Hilal, Ghofran (Dirasat: Human and Social Sciences, 2025)
Objectives: This study aims to explain the philosophy behind the development of women’s rights (WRs) at the international level, and the reasons behind the delay in integrating these rights within the framework of international law. The study also aims to analyze how international law incorporated WRs in the human rights (HRs) system. Methods: The study uses the descriptive analytical approach, by which the development of WRs at the international level is described and the factors that brought it to its current state are analyzed. The study relies on the historical approach, by studying the history of the WRs system at the international level. Results: The study concludes that the development of the WRs system occurred at a different pace than the HRs system, which affected the status of WRs internationally and nationally. It concludes that the establishment of the United Nations and the entry of women into the public field had the greatest impact on integrating WRs into the HRs system, and that the former is based on eliminating all forms of discrimination between men and women to reach genuine equality within the HRs system. Conclusions: The study recommends signing international WRs treaties and observing their requirements in line with the nature of local communities at the national level, and in cooperation with international efforts. It recommends that women be included in the international decision-making process, especially within legal committees, as the feminist perspective must be considered while drafting international law.